2019
DOI: 10.4054/demres.2019.40.4
|View full text |Cite
|
Sign up to set email alerts
|

The Healthy Immigrant Effect: The role of educational selectivity in the good health of migrants

Abstract: BACKGROUND The Healthy Immigrant Effect (HIE) refers to the fact that recent migrants are in better health than the nonmigrant population in the host country. Central to explaining the HIE is the idea that migrants are positively selected in terms of their socioeconomic and health characteristics when compared to nonmigrants in their country of origin. However, due to a lack of reliable and comparable data, most existing studies rely on socioeconomic and health measures as collected in the host country after m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
67
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(68 citation statements)
references
References 67 publications
0
67
1
Order By: Relevance
“…A similar argument can be applied to national contexts that differ in aggregate educational attainment (Feliciano 2005). While it has become relatively common to employ individuals' educational rank at origin as a proxy for pre-migration status (Ichou 2014;Spörlein and Kristen, 2018;Engzell 2019), here we extend the same approach to the destination country (cf., Feliciano and Lanuza 2017;Ichou and Wallace, 2019). We focus on two outcomes that are likely to be sensitive to reference group considerations: subjective social status and perceived financial situation.…”
Section: Reference Groups In Social Comparisonmentioning
confidence: 99%
“…A similar argument can be applied to national contexts that differ in aggregate educational attainment (Feliciano 2005). While it has become relatively common to employ individuals' educational rank at origin as a proxy for pre-migration status (Ichou 2014;Spörlein and Kristen, 2018;Engzell 2019), here we extend the same approach to the destination country (cf., Feliciano and Lanuza 2017;Ichou and Wallace, 2019). We focus on two outcomes that are likely to be sensitive to reference group considerations: subjective social status and perceived financial situation.…”
Section: Reference Groups In Social Comparisonmentioning
confidence: 99%
“…Despite a substantial between-study heterogeneity in refugees’ mental illness prevalence rates, forced migration has persistently been linked to increased rates of mental illnesses, chiefly, post-traumatic stress disorder (PTSD), depression, and anxiety disorder [ 5 7 ]. Even considering that those who embark on flight are likely to exhibit resilience (‘Healthy Immigrant Effect’ [ 8 ]), refugees are particularly at risk of facing psychological distress as sequelae of traumatic or stressful experiences before or during flight [ 4 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Empirical findings from a vast body of research have revealed several social factors that have a significant impact on immigrant birthweight. There is evidence that the socio-economic status, in terms of educational attainment and occupational position, has a positive impact on the health of mothers and their children through improved work and economic conditions, psycho-social resources, and healthy lifestyle choices [ 18 20 ]. However, this relationship can be curvilinear, with university-educated mothers presenting adverse birth outcomes likely due to their older age at delivery [ 6 ].…”
Section: Introductionmentioning
confidence: 99%